Instituting credibility, accountability and transparency in local service delivery? The Helpline and Aasthi in Karnataka, India - Mohan, Anjali K.; Cutrell, Ed; Parthasarathy, Balaji (in Proceedings of ICTD 2013, the 6th International Conference on Information and Communication Technologies and Development, 2013)
While e-governance is acclaimed as a means to decentralisation, and an efficiency and accountability enhancing mechanism, it can be implemented in different ways. In a strong centralized state like the Indian state, decentralization is often pursued in a centralized manner through top-down interventions. This paper, traces the implementation of two centrally driven e-governance interventions in the state of Karnataka, India i.e. Helpline and Aasthi to argue that while ‘centralized decentralization’ may be justified on grounds of standardization, it can have divergent outcomes, many of which are often contrary to the objectives of decentralization. The experience of Helpline and Aasthi belies the claim of e-governance being an efficiency and accountability enhancing mechanism. On the contrary, the centralized approach to decentralization in implementing Helpline and Aasthi has weakened the accountability of the state and limited the efficiency gains of urban decentralization.